(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Background: As we are aware that chronic liver disease frequently associated with haematological abnormalities whichpresents Anaemia of diverse etiology occurs in about 75% of patients and also this condition may be exacerbated bydeficiency of folic acid and/or vitamin B12 that can occur secondary to inadequate dietary intake or malabsorption. So Inthis study we want to evaluate chronic liver disease patients having anaemia without overt bleeding in the past 3 monthsto know the severity and type of anaemia in these patients so as to enable us better management and decrease associatedmorbidity and mortality.